Repotencialização de sistemas de distribuição rurais monofásicos por meio de dois cabos aéreos e o solo como a terceira fase - Borges, Paulo Roberto de Oliveira (2017)
In Brazil and in several countries of the world, rural electrification projects were developed using the single-phase system. Due to the type of loads of rural consumers and their dispersed location. With the growth of agribusiness as an activity that has contributed strongly to the national PIB, rural producers have been charging the authorities responsible for energy policy a positioning in the face of the demand for three-phase power in the countryside. The sector known as family agribusiness, now makes up 80% of food placed on the Brazilian table. Other activities in various sectors have, in their activities direct or indirect dependence on the products produced in the field, such as industry, commerce, services and transportation. The export sector, in particular, agricultural commodities has, in agribusiness its main agent that generates wealth for the country. In order for the agribusiness sector and small farmers, who are part of the chain of production can continue to grow, it is necessary to provide a quality, reliable three-phase electrical power system at an affordable cost. It is already known that electrifying the rural area with a conventional three-phase system is economically unfeasible. This study aims to collaborate with the insertion of the three-phase system in the field. To do this, a new design is suggested, by using the existing single-phase systems by means of a small adaptation. Transforming into a two-phase or three-phase system, the proposed system uses the earth as one of the phases. Theoretical analysis of the distribution system was modeled and simulated in ATPDraw software. A three-phase prototype low voltage, in order to verify in the field the operation of the proposed technique in this thesis was developed. The proposal is promising and represents a very attractive investment for the concessionaires, and a quick response to the agribusiness producer.